P12.02 Developing and using the eclinical care pathway framework: a novel tool for creating online clinical care pathways and its application to management of genital chlamydia. (13th September 2015) - Gibbs, J; Sutcliffe, LJ; Gkatzidou, V; Sonnenberg, P; Hone, K; Ashcroft, R; Harding-Esch, E; Lowndes, C; Sadiq, ST; Estcourt, CS
Abstract : Introduction: Home sexually transmitted infection (STI) sampling and remote STI diagnostics create potential for online treatment. Currently there is no guidance on development or content of online clinical consultations and, particularly, no recommendations relevant to sexual health. We describe creation of a new framework for developing complex online clinical care pathways and its application to management of people with genital chlamydia. Methods: We developed the eClinical Care Pathway Framework (eCCPF) consisting of a nine-step iterative process, Step 1: determines aims of the online clinical care pathway; Step 2: defines the functional units of the pathway; Step 3: drafts the online clinical consultation; Step 4: expert review; Step 5: comprehension testing; Step 6: user-centred interface testing; Step 7: specification development; Step 8: usability testing and further comprehension testing; Step 9: pilots the pathway. We then applied the framework to create the Chlamydia Online Clinical Care Pathway (Chlamydia-OCCP). Results: Using the eCCPF enabled us to elucidate the different sequence of functional units of care, as in contrast to traditional medicine, the Chlamydia-OCCP starts with provision of test results (diagnosis). Users then obtain infection-related information, before completing an online automated clinical consultation (medical and sexual history, partner notification), before collection of antibiotics from a community pharmacy. This enables a more focussed approach to assessment of safety of antibiotic prescribing than lengthier traditional medication history questions. Conclusion: By following each step of the eCCPF, the resulting Chlamydia-OCCP has a different sequence to traditional care pathways and is adapted to the needs of remote testing and online care. It provides the clinical services and surveillance functions required to meet UK national standards. This standardised method of collecting data on demography and sexual behaviour, with easily extractable data and potential for interoperability with surveillance systems, could be a powerful tool for public health and clinical management. Disclosure of interest statement: Nothing to declare.